Africa after the Cold War : the changing perspectives on security - Oyebade, Adebayo; Alao, Abiodun (Trenton, NJ : Africa World Press, 1998)
Although it is widely recognized that Africa's security problems are acute, it has never been a subject of much intellectual inquiry. This lack of scholarly discourse on the many dimensions of the problem of African security is the major consideration for this book. The approach to the question of security in this book differs markedly from the traditional approach that gives primacy to the threat of military aggression as sole factor in state security. A departure must be made from this dominant preoccupation in a new global order that has seen profound changes.
The authors then place primacy on the complex problems of ethno-religious nationalism, economic stagnation, catastrophic civil wars, environmental degradation and the prospects for democratic structures in considering Africa's security issues after the Cold War.
Redefining African security / Adebayo Oyebade and Abiodun Alao -- Economic development and the prospect for economic security in Africa / Victor Oguejiofor Okafor and Sheriffdeen A. Tella -- Democracy and security in Africa / Amadu Sesay and Abiodun Alao -- The environment and African security / Abiodun Alao -- African security and nuclear weapons / Adebayo Oyebade -- Post Cold War Africa / Abiodun Alao and Funmi Olonisakin -- The end of the Cold War in Africa / Adebayo Oyebade -- Beyond the Cold War / Ayele Bekerie -- A short peep into a long future / Adebayo Oyebade and Abiodun Alao.
Includes bibliographical references (pages 209-224) and index.
Keywords: African Union; Since 1900; National security -- Africa -- History -- 20th century; regional security; 89.90 foreign policy; History